PERAN KEPUASAN MEMEDIASI KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP WOM PADA LAYANAN GO-JEK DI DENPASAR - Somantari, Made Ayu; Rastini, Ni Made (E-Jurnal Manajemen; Vol 8 No 4 (2019)DO - 10.24843/EJMUNUD.2019.v08.i04.p21, 2019)
This study is aimed to analyse the impact of service quality, price perception, to word of mouth (WOM) through customer satisfaction as intervening. The study was conducted at Denpasar, Bali with a population all customers of Go-Jek transportation service and the sample size of 100 respondens. The data were collected by distributing questionnaires and using a Likert scale to measure 15 indicators. The analysis technique used in this research is path analysis, accompanied by classical assumption tests and Sobel test. The result of this study indicates that service quality and price perception has a positive and significant effect to customer satisfaction, service quality and price perception has a positive and significant effect towards WOM, customer satisfaction has a positive and significant effect towards WOM and customer satisfaction positively and signifianly mediatesthe effect of service quality and price perception to WOM. The results also showed that satisfaction is able to mediate the effect of service quality and price perception towards the positive WOM. Keywords : service quality, price perception,customer  satisfaction, word of mouth